2015
DOI: 10.1248/cpb.c15-00037
|View full text |Cite
|
Sign up to set email alerts
|

Eleven Microbial Metabolites of 6-Hydroxyflavanone

Abstract: Structures of the metabolic products were elucidated by means of spectroscopic data. None of the metabolites tested showed antibacterial, antifungal and antimalarial activities against selected organisms. However, weak antileishmanial activity was observed for metabolite 11 when tested against Leishmania donovani.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, one of the quercetin derivatives has proven to have a protective effect on the intact β-cells of the islets of Langerhans by inhibiting lipid peroxidation, as well as its ability to scavenge free radicals from STZ-induced oxidative stress in STZ-induced diabetic rats [ 20 ]. Although no research has been conducted regarding the proficiency of 6-hydroxyflavanone on directly reducing the blood glucose level, there are some studies that have demonstrated the electron donating ability of 6-hydroxyflavanone to scavenge free radicals induced by 2,2-diphenyl-1-picrylhydrazyl in in vitro antioxidant study [ 21 , 59 ]. Besides that, kaempferol, another flavonoid-type compound that was identified and quantified, also reportedly shows hypoglycemic effect by lowering the levels of glycoprotein in the liver and increment of insulin production, as well as enhancement of glucose utilization in STZ-induced rats [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one of the quercetin derivatives has proven to have a protective effect on the intact β-cells of the islets of Langerhans by inhibiting lipid peroxidation, as well as its ability to scavenge free radicals from STZ-induced oxidative stress in STZ-induced diabetic rats [ 20 ]. Although no research has been conducted regarding the proficiency of 6-hydroxyflavanone on directly reducing the blood glucose level, there are some studies that have demonstrated the electron donating ability of 6-hydroxyflavanone to scavenge free radicals induced by 2,2-diphenyl-1-picrylhydrazyl in in vitro antioxidant study [ 21 , 59 ]. Besides that, kaempferol, another flavonoid-type compound that was identified and quantified, also reportedly shows hypoglycemic effect by lowering the levels of glycoprotein in the liver and increment of insulin production, as well as enhancement of glucose utilization in STZ-induced rats [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…M. calabura mainly consists of several compounds, such as triterpenoids (lupenone); flavonoids (5,7-dihydroxyflavanone, 7-hydroxyflavanone, 5-hydroxy-3,7,8-trimethoxyflavone, 5′-hydroxy-7,8,3′,4′-tetramethoxyflavan, 3,5-dihydroxy-7,4′-dimethoxyflavone); phytosterols (β-sitostenone and β-sitosterol), and chalcones derivatives (2′,4′-dihydroxydihydrochalcone, 2′,4′-dihydroxychalcone, and isoliquiritigenin) [ 15 , 16 , 17 ]. Several studies have compiled the health benefits of these constituent compounds in ameliorating the diabetic complications [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…6HF has pharmacologically significant biological characteristics such as neuroprotection, antimicrobial, anti-inflammatory, anticancer, and antioxidants and has been discovered to be an effective treatment for diabetic patients against glomerulonephritis and glomerulosclerosis (Iwakiri et al, 2013;Wang et al, 2015;Das et al, 2018;Das et al, 2019;Stompor et al, 2019;Wang et al, 2021). Stompor et al (2019) and Mikell et al (2015) revealed that the hydroxyl group or the propionyl group located in the A ring of the flavones at the C-6 positions has an inhibitory effect on hormone production in the process of steroidogenesis and has cytotoxic solid and apoptotic activities against cancer cell (Iwakiri et al, 2013;Mikell et al, 2015;Wang et al, 2015;Stompor et al, 2019). A hydroxyl group at the sixth carbon in the 6HF compound chemical structure makes 6HF easily esterifiable.…”
Section: Introductionmentioning
confidence: 99%